Safety of a feed additive consisting of semduramicin sodium (Aviax 5%) for chickens for fattening (Phibro Animal Health s.a.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Fašmon Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2022)
Abstract Following a request from the European Commission, the Panel on Additives and Products or substances used in Animal Feed (FEEDAP Panel) was asked to deliver a scientific opinion on the safety of the coccidiostat Aviax 5% (semduramicin sodium) when used in feed for chickens for fattening. In a previous assessment, the FEEDAP Panel could not conclude on the taxonomical identification of the production strain at species level and on the absence of genetic determinants for antimicrobial resistance. In addition, the Panel could not conclude on the safety for the target animals and could not set maximum residue limits to protect consumers. Regarding the safety for the environment, although the use of the additive was considered safe for the terrestrial compartment, a risk for the aquatic compartment and for groundwater pollution could not be excluded. Based on the new data provided, the FEEDAP Panel concludes that there are no safety concerns for the target animals, consumer, user and environment regarding the production strain of semduramicin sodium. Based on the results in the tolerance trial, the FEEDAP Panel concludes that the additive is safe for chickens for fattening up to the maximum recommended level (25 mg/kg complete feed), but no margin of safety can be established. The use of semduramicin sodium at a maximum level of 25 mg/kg complete feed for chickens for fattening is safe for consumers with no withdrawal time. Based on the new data provided and the current requirements for environmental risk assessment, the use of semduramicin sodium from Aviax 5% in feed for chickens for fattening up to 25 mg/kg complete feed does not pose a risk for groundwater nor for aquatic and sediment compartments, while a risk for the terrestrial compartment cannot be excluded. The bioaccumulation and the risk for secondary poisoning are considered to be low.